2022
DOI: 10.3390/cancers14184503
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of Oxidative Phosphorylation-Related Subtypes, Establishment of a Prognostic Signature and Immune Infiltration Characteristics in Colorectal Adenocarcinoma

Abstract: Oxidative phosphorylation (OXPHOS) is an emerging target in cancer therapy. However, the prognostic signature of OXPHOS in colorectal adenocarcinoma (COAD) remains non-existent. We comprehensively investigated the expression pattern of OXPHOS-related genes (ORGs) in COAD from public databases. Based on four ORGs, an OXPHOS-related prognostic signature was established in which COAD patients were assigned different risk scores and classified into two different risk groups. It was observed that the low-risk group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Next, we sought to investigate the molecular mechanism. In colorectal cancer, forty-two OXPHOS-related genes were differentially expressed between tumor and normal samples, with 8 genes showing prognostic value 39 . Combined with our sequencing data, we identified that one target, PPARGC1A , was significantly upregulated in recipient cells treated with Res-exos (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we sought to investigate the molecular mechanism. In colorectal cancer, forty-two OXPHOS-related genes were differentially expressed between tumor and normal samples, with 8 genes showing prognostic value 39 . Combined with our sequencing data, we identified that one target, PPARGC1A , was significantly upregulated in recipient cells treated with Res-exos (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…The "limma" software package was used to analyze the differentially expressed genes (DEGs) between the two m6A clusters with thresholds of |log2FC|≥ 1 and FDR ≤ 0.05. We used "clusterProfiler" to perform GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) functional enrichment analyses to explore the potential biological functions of these DEGs 28 .…”
Section: Methodsmentioning
confidence: 99%
“… 224 In GBM, IGF2BP2 was involved in maintaining stability of SHMT2 mRNA, which played a crucial role in OXPHOS activities, as a significant driving force of GBM tumorigenesis. 350 Elevated m6A level and IGF2BP2 expression conduced to maintenance of hematopoietic stem cells (HSCs) via restricting mitochondrial activity. IGF2BP2 deficiency accelerated degradation of Bmi1 mRNA, relieving its depression on mitochondria-related genes, thus impaired quiescence state and functions of HSCs.…”
Section: Rna Modifications and Cellular Metabolismmentioning
confidence: 99%